Biological Monitoring of heavy metals (Pb, Cd, Fe, Zn, Ni, Cu) by tissues of Capoeta damascina from Sezar river, Lorestan province - A. Farhadi email ; V. Yavari (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2013)
This study was carried out in order to measure and compare heavy metals levels (Pb,Cd,Fe, Zn, Ni and Cu) in gill and muscle of Capoeta damascina. 60 fish were caught from 3 stations in Tangeh haft zone from Sezar river. Heavy metals were measured by Atomic Absorption spectrophotometery. The highest concentrations of heavy metals Fe>Zn>Pb>Ni>Cu>Cd, respectively. The average heavy metals concentration in gill and muscle have significant different (P0.05). The results of this study showed that there were significant difference between heavy metals concentrations in gill, liver and muscle (P